Morphological Indicators Related to Age in Carp Fish - Yuldoshev X. T (American Journal of Biodiversity, 2025)
This article presents the results of a comparative analysis of biological indicators of silver carp cultivated in various ecological zones of Uzbekistan. The study examined parameters such as standard body length (cm), total weight (g), eviscerated weight (g), individual absolute fecundity (thousand eggs), and individual relative fecundity (eggs/g). Monthly and regional (district-level) comparisons revealed that ecological factors and seasonal changes significantly influence fecundity and morphometric characteristics. These findings are important for improving selective breeding practices and ensuring the sustainable use of biological resources in aquaculture.